pH-Induced changes in adsorbed cytochrome c. voltammetric and surface-enhanced resonance Raman characterization performed simultaneously at chemically modified silver electrodes - Millo, Diego (Langmuir : the ACS journal of surfaces and colloids, 2007)
The influence of pH on the redox properties of cytochrome c (cyt c) adsorbed on roughened silver electrodes chemically modified with a self-assembled monolayer (SAM) of 11-mercapto-1-undecanoic acid (MUA) was studied with voltammetric techniques in combination with surface-enhanced resonance Raman scattering (SERRS). The experiments were performed simultaneously on the same electrode sample in a homemade spectroelectrochemical cell suitable for such applications. At pH 7.0 cyt c was found in its native state; at higher pH values (ranging from 8.0 to 9.0) the redox properties of the adsorbed protein varied considerably, featuring a redox behavior which does not resemble the one reported for the alkaline transition. Our results instead indicate the presence of an electrochemically inactive 6cLS species immobilized on MUA at pH 9.0. The pH-induced conformational changes observed for cyt c immobilized on the SAM of MUA were found to be repeatable and chemically reversible, meaning that the recovery of the electrochemical signal due to the native protein occurred instantaneously (on the second time scale) when the electrode was switched back to pH 7.0. The pH-induced changes observed were attributed to a conformational change involving a heme reorientation with respect to the electrode surface